Pharmacokinetic interactions between primaquine and chloroquine. - Pukrittayakamee, S; Tarning, J; Jittamala, P; Charunwatthana, P; Lawpoolsri, S; Lee, S; Hanpithakpong, W; Hanboonkunupakarn, B; Day, N; Ashley, E; White, N (2014)
Chloroquine combined with primaquine has been the standard radical curative regimen for Plasmodium vivax and Plasmodium ovale malaria for over half a century. In an open-label crossover pharmacokinetic study, 16 healthy volunteers (4 males and 12 females) aged 20 to 47 years were randomized into two groups of three sequential hospital admissions to receive a single oral dose of 30 mg (base) primaquine, 600 mg (base) chloroquine, and the two drugs together. The coadministration of the two drugs did not affect chloroquine or desethylchloroquine pharmacokinetics but increased plasma primaquine concentrations significantly (P ≤ 0.005); the geometric mean (90% confidence interval [CI]) increases were 63% (47 to 81%) in maximum concentration and 24% (13 to 35%) in total exposure. There were also corresponding increases in plasma carboxyprimaquine concentrations (P ≤ 0.020). There were no significant electrocardiographic changes following primaquine administration, but there was slight corrected QT (QTc) (Fridericia) interval lengthening following chloroquine administration (median [range] = 6.32 [-1.45 to 12.3] ms; P < 0.001), which was not affected by the addition of primaquine (5.58 [1.74 to 11.4] ms; P = 0.642). This pharmacokinetic interaction may explain previous observations of synergy in preventing P. vivax relapse. This trial was registered at ClinicalTrials.gov under reference number NCT01218932.